2017
DOI: 10.1136/bmjopen-2016-015032
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of mitral valve repair with leaflet resection versus leaflet preservation on functional mitral stenosis (The CAMRA CardioLink-2 Trial)

Abstract: BackgroundThe gold-standard treatment of severe mitral regurgitation (MR) due to degenerative disease is valve repair, which is surgically performed with either a leaflet resection or leaflet preservation approach. Recent data suggest that functional mitral stenosis (MS) may occur following valve repair using a leaflet resection strategy, which adversely affects patient prognosis. A randomised comparison of these two approaches to mitral repair on functional MS has not been conducted.Methods and analysisThis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The Canadian Mitral Research Alliance (CAMRA) Randomized Controlled Trial (ClinicalTrials.gov; NCT02552771), a prospective trial comparing the incidence of functional mitral stenosis with resection versus neo-chordal repair, is currently enrolling patients and will shed light on this important issue. 40 Another interesting finding from this study is the higher postprocedural LVEF in the neo-chord group, which reached statistical significance in the RCT but not in the 2 observational studies that reported this outcome. The rationale for chordal techniques involves ''respecting'' the normal valvular geometry, which is intimately tied to left ventricular function.…”
Section: Discussionmentioning
confidence: 60%
“…The Canadian Mitral Research Alliance (CAMRA) Randomized Controlled Trial (ClinicalTrials.gov; NCT02552771), a prospective trial comparing the incidence of functional mitral stenosis with resection versus neo-chordal repair, is currently enrolling patients and will shed light on this important issue. 40 Another interesting finding from this study is the higher postprocedural LVEF in the neo-chord group, which reached statistical significance in the RCT but not in the 2 observational studies that reported this outcome. The rationale for chordal techniques involves ''respecting'' the normal valvular geometry, which is intimately tied to left ventricular function.…”
Section: Discussionmentioning
confidence: 60%
“…5 Randomized trials of neochords versus resection techniques show clinical equivalence. 6 I do not use neochords because they require judgment and a little "art" in surgery, but I admit that is my opinion. Sometimes when I do a reoperation for failed neochord repair, the valve looks like a Picasso portrait-not a good look for a mitral valve.…”
mentioning
confidence: 99%
“…These data are an update of the initial trial report. 2 Other studies have compared the resect versus respect repair techniques, but there has been only 1 other randomized trial. 3 In terms of new data comparing LV volumes after resect versus respect repairs, this is a negative study with no differences seen.…”
Section: Donald Glower MDmentioning
confidence: 99%